Proposal for a Hypothetical Learning Path Using GeoGebra in Learning Numerical Sequences - Jaime Cuauhtémoc Negrete (Research and Advances in Education, 2024)
A hypothetical learning path is proposed for the teaching-learning of numerical sequences in second grade secondary school students, it is theoretically based in a Duval’s Theory of Semiotic Representation Registers and methodologically based on GeoGebra & Hypothetical Learning Path. It is intended to contribute to this field of mathematics given that there are not many the works in this regard, a fact that motivates the facilitation of better perspectives for students in learning the mathematical object numerical sequences. According to the hypothetical learning trajectory theory, each stage of learning requires a series of preconditions and appropriate instructional approaches so that the individual can progress. These stages include: 1) Acquisition of basic knowledge 2) Application of skills 3) Automation 4) Integration. It is concluded that it must be applied in the classroom to know the effectiveness of this trajectory.